A Working Model for Mobile Charging using Wireless Power Transmission - Joe Louis Paul, I; Sasirekha, S; Naveen Kumar D, D; S. Revanth, P (International Journal of Engineering and Technology, 2018)
Portable electronic devices are very popular nowadays. Almost all portable devices are battery powered, meaning that eventually, they all must be recharged–using the wired chargers currently being used. As the usage of these portable electronic devices is increasing, the demands for longer battery life are also increasing. These batteries need to be recharged or replaced periodically. It is a hassle to charge or change the battery after a while, especially when there is no power outlet around. Now instead of plugging in a cell phone, Personal Digital Assistant (PDA), digital camera, voice recorder, mp3 player or laptop to recharge it, it could receive its power wirelessly. The technology for Wireless Power Transmission or Wireless Power Transfer or Transmission (WPT) is in the forefront of electronic development. WPT systems are designed to transmit power without using wires more efficient than transmitting it while using wires. There could be large number of applications for wireless power systems. Hence, in this work, a wireless battery charger has been proposed for mobile phone charging which is expected to eliminate all the hassles with today’s battery technology. The advantage of this device is that it can wirelessly charge up the batteries which can save time and money in a long run for the general public.